2016
DOI: 10.1074/jbc.m115.669812
|View full text |Cite
|
Sign up to set email alerts
|

α-Defensins Induce a Post-translational Modification of Low Density Lipoprotein (LDL) That Promotes Atherosclerosis at Normal Levels of Plasma Cholesterol

Abstract: Approximately one-half of the patients who develop clinical atherosclerosis have normal or only modest elevations in plasma lipids, indicating that additional mechanisms contribute to pathogenesis. In view of increasing evidence that inflammation contributes to atherogenesis, we studied the effect of human neutrophil ␣-defensins on low density lipoprotein (LDL) trafficking, metabolism, vascular deposition, and atherogenesis using transgenic mice expressing human ␣-defensins in their polymorphonuclear leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 42 publications
3
45
0
Order By: Relevance
“…presentation support the potential contribution of HNP-mediated inhibition of ADAMTS13 activity to the pathogenesis of acquired autoimmune TTP and identifies a potential new therapeutic target such as colchicine to inhibit the release of HNPs 33 in the treatment and prevention of disease relapse.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…presentation support the potential contribution of HNP-mediated inhibition of ADAMTS13 activity to the pathogenesis of acquired autoimmune TTP and identifies a potential new therapeutic target such as colchicine to inhibit the release of HNPs 33 in the treatment and prevention of disease relapse.…”
Section: Discussionsupporting
confidence: 52%
“…by guest www.bloodjournal.org From induce a post-translational modification of low-density lipoprotein that promotes atherosclerosis at normal levels of plasma cholesterol. 33 Here, we show that HNPs inhibit the proteolytic cleavage of the minimal substrate VWF73 and multimeric VWF by ADAMTS13 under diverse conditions (Figures 1 and 2). This inhibitory activity appeared to be mediated by high-affinity binding of HNPs to the central A2 domain of VWF (ie, VWF73) through the RRY motif (Figure 3).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…More specifically, results from several groups using diverse approaches suggest that human α-defensins (α-defs) 1-4, also known as human neutrophil peptides (HNPs), [2] contribute to this process [5,6,[8][9][10][11]. We recently examined the mechanism by which α-defensins released from activated neutrophils may promote formation of lipid streaks in the vasculature using HNP-1tg/tg Def +/+ (Def +/+ ) mice fed a high fat diet (HFD) [12]. We found that α-defensin-1 (α-def-1) forms complexes with LDL, accelerating lipoprotein clearance from the circulation by the liver, leading to hypocholesterolemia [12].…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%
“…We recently examined the mechanism by which α-defensins released from activated neutrophils may promote formation of lipid streaks in the vasculature using HNP-1tg/tg Def +/+ (Def +/+ ) mice fed a high fat diet (HFD) [12]. We found that α-defensin-1 (α-def-1) forms complexes with LDL, accelerating lipoprotein clearance from the circulation by the liver, leading to hypocholesterolemia [12]. In line with this, plasma levels of total cholesterol (TCH) and LDL were lower in Def +/+ mice than in wild type control animals [12].…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 99%